Effect of hyperbaric oxygen on oxygen uptake and measurements in the blood and tissues in a normobaric environment - Hodges, A. N. H.; Delaney, S.; Lecomte, J. M.; Lacroix, V. J.; Montgomery, D. L. (British Journal of Sports Medicine, 2003)
Objective: To examine venous partial pressure of oxygen (PvO2), transcutaneous oxygen tension (tcPO2), and VO2MAX in a normobaric environment after a single hyperbaric oxygen (HBO2) treatment. Methods: This was a prospective study of conditions after the intervention compared with baseline. The participants were 10 moderately trained (VO2MAX = 57.6 ml/kg/min) men. Two HBO2 treatments consisting of breathing 95% oxygen at 2.5 atmospheres absolute (ATA) for 90 minutes were administered on non-consecutive days. Baseline testing included measures of VO2MAX, tcPO2, and anthropometry. At 6.0 (1.0) minutes after the first HBO2 treatment, a VO2MAX test was performed. After the second HBO2 treatment, leg and chest tcPO2 and PvO2 were monitored for 60 minutes. Results: VO2MAX, running time, and peak blood lactate were not altered after the HBO2 treatment. Leg tcPO2 was lower (p = 0.003) and chest tcPO2 was unchanged after the HBO2 treatment compared with baseline values. PvO2 was significantly (p<0.001) lower in the first three minutes after treatment than subsequent values, but no other differences were found. Conclusions: A single HBO2 treatment at 2.5 ATA for 90 minutes does not raise PvO2, tcPO2, or VO2MAX in a normobaric, normoxic environment.